Impact of low-load blood flow restriction training on knee osteoarthritis pain and muscle strength: a systematic review and meta-analysis of randomized controlled trials - Lin, Qiuxiang; Yu, Debiao; Zhang, Yuping; Chen, Xiaoting; Qin, Jiawei; Wu, Fuchun (Frontiers in Physiology, 2025)
ObjectivesThe effectiveness of low-load blood flow restriction training (LL-BFRT) in alleviating symptoms in patients with knee osteoarthritis (KOA) remains inconclusive. This systematic review and meta-analysis aim to comprehensively assess the effects of LL-BFRT compared to conventional resistance training on pain, muscle strength, and functional capacity in individuals with KOA.Data sourcesPubMed, Embase, Web of Science, EBSCO, Scopus, and Cochrane trails were searched.Study selectionWe included randomized controlled trials involving patients with KOA, in which the intervention group underwent LL-BFRT.Data extractionLiterature quality and risk of bias were assessed using the Physiotherapy Evidence Database (PEDro) scale and the Cochrane Risk-of-Bias Tool (ROB 2). Data were extracted using a predefined table, including outcomes such as pain, quadriceps muscle strength, 30-s sit-to-stand test (30STS) and Timed Up and Go test (TUG).ResultTen studies were included in the meta-analysis. The pooled results indicated that, compared to conventional resistance training, LL-BFRT significantly improved knee joint pain [SMD = 0.25, 95%CI (0.02, 0.48), P = 0.03], increased quadriceps muscle strength [SMD = 0.46, 95%CI (0.04, 0.88), P = 0.03], and enhanced performance on the 30s sit-to-stand test (30STS) [WMD = 1.71, 95%CI (0.30, 3.11), P = 0.02]. However, no significant difference was observed in the improvement of the Timed Up and Go test (TUG) [WMD = −0.13, 95%CI (−0.51, 0.24), P = 0.49]. Subgroup analysis revealed that interventions with an occlusion pressure >100 mmHg and a duration ≤6 weeks had a significant impact on pain relief, quadriceps muscle strength, and the 30STS performance. For patients with KOA aged >65 years, LL-BFRT was more effective in alleviating pain, while for patients aged ≤65 years, it demonstrated more significant improvements in quadriceps strength and 30STS performance.ConclusionLimited evidence suggests that LL-BFRT may be more effective than conventional resistance training in improving pain, quadriceps muscle strength, and 30STS performance in patients with KOA, while exhibiting a comparable effect on TUG test.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD42024603542